Paradigma Pemikiran Fikih Sosial K.H. Sahal Mahfud dalam Bidang Hukum Keluarga - Tahir, Masnun (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
The social fiqh by KH. Sahal Mahfudh discuss mainly in family problems. He develops a critical thinking in understanding the classical kitab. It is stated that it would be better for understanding the classical kitab with the proportional methods in order to get the contextualization and the appropriateness with the reality, especially in family cases.